The Intestinal Microbiome in Early Life: Health and Disease - Arrieta, Marie-Claire; Stiemsma, Leah T.; Amenyogbe, Nelly; Brown, Eric M.; Finlay, Brett (Frontiers in Immunology, 2014)
Human microbial colonization begins at birth and continues to develop and modulate in species abundance for about three years, until the microbiota becomes adult-like. During the same time period, children experience significant developmental changes that influence their current health status as well as their immune system. An ever-expanding number of articles associate several diseases with early life imbalances of the gut microbiota, also referred to as gut microbial dysbiosis. Whether early life dysbiosis precedes and plays a role in disease pathogenesis, or simply originates from the disease process itself is a question that is beginning to be answered in a few diseases, including IBD, obesity and asthma. This review describes the gut microbiome structure and function during the formative first years of life, as well as the environmental factors that determine its composition. It also aims to discuss the recent advances in understanding the role of the early life gut microbiota in the development of immune-mediated, metabolic, and neurological diseases. A greater understanding of how the early life gut microbiota impacts our immune development could potentially lead to novel microbial-derived therapies that target disease prevention at an early age.